The Interaction of Facial Expression and Donor-Recipient Eye Contact in Donation Intentions: Based on the Intensity of Emotion - Tong, Zelin; Yi, Mengjie; Feng, Wenting; Yu, Yinghao; Liu, Diyi; Zhang, Jixuan (Frontiers in Psychology, 2021)
Both happy and sad facial expressions of recipients are frequently used in charity advertisements. However, the relative effectiveness of these two types of facial expressions has been found paradoxical in the past. In this study, we examine when happy facial expression can more effectively increase consumers’ donation intentions and when vice versa. Specially, we propose that eye contact between donor and a potential recipient may moderate the relative effectiveness of happy and sad facial expression, and further explain the interaction effect from the perspective of emotional intensity. Results from two experiments suggest that when donor-recipient eye contact is present, consumers tend to have stronger emotional intensity, and, in turn, show higher donation intentions when the recipient is with a happy rather than sad facial expression. In contrast, when the eye contact is absent, consumers may show stronger emotional intensity and donation intentions towards the charity advertisement with a recipient showing sad rather than happy expression.